An experimental study on the reproducibility of different multilayer OLED materials processed by slot die coating. (16th March 2017) - Raupp, S.M.; Merklein, L.; Pathak, M.; Scharfer, P.; Schabel, W.
Abstract: In this work we aim at solution-processed multilayer organic light emitting diodes (OLEDs) with slot die coating as a scalable technology. We apply small molecules, polymers and polymer-host systems as emissive layers. The emissive layers are slot die coated on slot die coated Pedot:PSS. All experiments are performed with commercially available materials, aiming to establish a fundamental knowledge about processing these different materials from solution. The coating was carried out on indium tin oxide glass substrates with a table coater under ambient conditions. The focus is on the reproducibility and the processing itself. Several batches of OLEDs were produced for reproducibility and averaged values of 200 OLEDs in total were measured to ensure the reliability of the data. We demonstrate devices with two slot die coated organic layers reaching ~ 5 cd/A at low standard deviation. Graphical abstract: Highlights: Slot die coated OLED stack of two organic layers. Investigation of a various number of EML materials. Slot die coating of polymer, small molecule solutions and dispersions. Visco-capillary model applied for six different coating solutions. Proven reproducibility with 200 OLEDs of two different sizes.